Strategic Political Communication and Propaganda: Gibran RakabumingRaka’s Message Formulation in the 2024 Vice Presidential Campaign - Mutiara, Mutiara; Nastain , M (Lingkar Studi Komunikasi (LISKI), 2025)
Gibran Rakabuming Raka's nomination as vice president in the 2024 election has invited pros and cons. Strong propaganda in the formulation of messages given by Gibran has received much attention from the public, as seen in the news on the internet and social media. So the victory of Gibran and his partner is interesting to study. This study aims to determine the formulation of messages in strong propaganda carried out by Gibran in the political campaign in the 2024 election. This research method uses a qualitative method on secondary data obtained from various sources, such as journals, survey or research results, news portals, books, reports, and other data sources. Secondary data collection is done through the documentation method. The theory used is the theory of message formulation by Alan H Monroe (1930) "motivated sequence", there are five steps in the formulation of messages, namely Attention, Need, Satisfaction, Visualization, and Action. The results of this study show a correlation with the theory used, where the preparation of strong propaganda messages carried out by Gibran can make him the winner of the presidential election activities with his partner in the 2024 election.